Study of Optical Cloaking Lenses Design for Optimizing Large Vehicle Driver’s Visibility in Bandar Lampung - O. F. Tri Maryana; L. Y. Ginting; F. Pahlawan; M. Y. Darmawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Nowadays, invisibility efforts by scientists and engineers have focused on building a large broadband, multidirectional cloaking device. The device is usually a cloak that works in macroscopic dimensions and for the entire visible spectrum. Addition with the full-field of light, no new materials, simple infrastructure, and scale easily may be considered an ‘ideal’ cloaking device. This paper report of implementing ray optics cloaking formalism presented previously by Choi and Howell [1] using lenses design for cloaking arbitrarily large, and moving objects such as large vehicle. We apply their formalism using simulation and experiment scheme to general optical systems up to four convex lenses. The results support the information to create optical cloaking prototype for optimizing large vehicle driver’s visibility as alternative solution for decreasing traffic accident in Bandar Lampung.